2020
DOI: 10.1038/s41598-020-69116-6
|View full text |Cite
|
Sign up to set email alerts
|

Sources of solutes and carbon cycling in perennially ice-covered Lake Untersee, Antarctica

Abstract: perennially ice-covered lakes that host benthic microbial ecosystems are present in many regions of Antarctica. Lake Untersee is an ultra-oligotrophic lake that is substantially different from any other lakes on the continent as it does not develop a seasonal moat and therefore shares similarities to sub-glacial lakes where they are sealed to the atmosphere. Here, we determine the source of major solutes and carbon to Lake Untersee, evaluate the carbon cycling and assess the metabolic functioning of microbial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 69 publications
0
17
0
Order By: Relevance
“…For example, a diverse community of diatoms including, Navicula , Nitszchia , and Diadesmis have been reported in lakes Hoare ( Spaulding et al, 1997 ), Fryxell ( Jungblut et al, 2016 ) and Vanda ( Sumner et al, 2016 ). In Lake Untersee, the paucity of diatoms has been linked to the extreme high pH ( Andersen et al, 2011 ), which has been linked to weathering of clay minerals in an ice-sealed water body ( Wand et al, 1997 ; Andersen et al, 2011 ; Marsh et al, 2020 ). High pH extends many millimeters into the mat surface in Lake Untersee ( Hawes et al, 2019 ) and this has been shown to constrain growth in diatoms ( Chen and Durbin, 1994 ), although there are examples of diatoms tolerant of high pH ( Sutherland, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a diverse community of diatoms including, Navicula , Nitszchia , and Diadesmis have been reported in lakes Hoare ( Spaulding et al, 1997 ), Fryxell ( Jungblut et al, 2016 ) and Vanda ( Sumner et al, 2016 ). In Lake Untersee, the paucity of diatoms has been linked to the extreme high pH ( Andersen et al, 2011 ), which has been linked to weathering of clay minerals in an ice-sealed water body ( Wand et al, 1997 ; Andersen et al, 2011 ; Marsh et al, 2020 ). High pH extends many millimeters into the mat surface in Lake Untersee ( Hawes et al, 2019 ) and this has been shown to constrain growth in diatoms ( Chen and Durbin, 1994 ), although there are examples of diatoms tolerant of high pH ( Sutherland, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…The feldspar was shown to be Ca plagioclase, and the clays minerals typically had a Al:Si:O mole ratio of 1:2:5–6 ( Andersen et al, 2011 ). The organic C abundances of the microbial mats is 10.14% in the upper pigmented sections (0 – 0.5 cm) (Andersen, unpublished data) and range from 1.0 to 5.8 % in the lower laminations, decreasing with depth within the mats ( Marsh et al, 2020 ). Microbial mats have been observed to extend from 8 to 130 m deep in the lake; pinnacles were observed at depths up to around 20 m whilst cones were observed regularly throughout the lake to depths of 130 m ( Figure 1B ).…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that terrestrial carbon subsidies make an important contribution to seasonal trends in microbial communities in the mountain lakes. TOC can be utilized by aquatic heterotrophic microorganisms [25,26]. Because organic carbon is an important energy material for heterogeneous microorganisms, changes in organic carbon lead to changes in protistan community structure.…”
Section: Effects Of Seasonal Freezing-thawing On Protistan Communitiesmentioning
confidence: 99%
“…The presence of the boulders is evidence for the presence of a thick, continuous ice cover for at least the past hundred years or perhaps throughout the Holocene 20 . The lake is recharged entirely by subaqueous melting of glacial ice and subglacial meltwater 21 , and it has a Na(Ca)-SO 4 geochemical facies with high pH (10.6) that reflects a heritage of recharge from glacial meltwater, with minor contribution of Ca 2+ -Na + solutes from in situ weathering of plagioclase and aluminosilicate minerals 22 . The total inorganic carbon (TIC) and total organic carbon (TOC) concentrations in the lake are very low (0.3-0.4 mg C L −1 ) 22 , 1-3 orders of magnitude lower than in the MDV lakes and Antarctic subglacial lakes [23][24][25][26] .…”
mentioning
confidence: 99%